Ternary precursor with vertically stacked primary particles as well as preparation method and application of ternary precursor
By adjusting the bottom liquid composition and reaction conditions during the preparation of the ternary precursor, the vertical accumulation of primary particles is achieved, and the problems of insufficient lithium ion transmission path length and mechanical strength in the prior art are solved, and the rate performance and service life of the battery are improved.
Patent Information
- Application Number
- CN202411819759.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-11
AI Technical Summary
The prior art fails to have both a ternary precursor that shortens the lithium ion transmission path and improves mechanical strength.
In the process of preparing the ternary precursor, specific base liquid components and reaction conditions are adopted, including increasing the rotation speed and ammonia concentration in step 2 and increasing the concentration of the mixed metal salt solution in step 3 to achieve vertical accumulation of primary particles.
The lithium ion channel is optimized, the lithium ion transmission path is shortened, the battery's rate performance is improved, and the battery's service life is extended by improving the pressure withstand strength.
Smart Images

Figure CN119683705A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a ternary precursor with vertically stacked primary particles, and a preparation method and application thereof. Background Art
[0002] Ternary precursors are important compounds for manufacturing positive electrode materials for lithium-ion batteries, which directly affect the energy density, rate performance, cycle life and safety performance of the battery. In terms of elemental effects, nickel can increase energy density, cobalt can enhance material stability, and manganese can help reduce costs and improve safety. The industrialization of precursors mainly adjusts the ratio of nickel, cobalt and manganese to obtain nickel-cobalt-manganese ternary positive electrode materials with different performances to meet different application requirements.
[0003] Primary particles refer to single crystal grains formed during the precursor synthesis process, which are crucial to the electrical properties of the final electrode material. The stacking mode and morphology of primary particles will affect the ion channel of the electrode material. The shorter the ion channel of the electrode material of the same size, the more conducive it is to the diffusion rate of lithium ions in the electrode material, thereby improving the rate performance of the battery. In addition, the mechanical strength of primary particles will affect the structural stability of the electrode material during the cycle. Higher mechanical strength can reduce the micro cracks generated in the electrode material during charging and discharging, thereby extending the battery life.
[0004] At present, there is no ternary precursor that can both shorten the lithium ion transmission path and improve the mechanical strength.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The purpose of the present invention is to provide a ternary precursor with vertically stacked primary particles and a preparation method and application thereof, so as to solve or improve the above-mentioned technical problems.
[0007] The present invention can be implemented like this: In a first aspect, the present invention provides a method for preparing a ternary precursor with primary particles vertically stacked, wherein the chemical formula of the ternary precursor is Ni x Co y Mn 1-x-y (OH)2, where 0.5≤x≤0.8, 0.02≤y≤0.35, x+y<1; The preparation of the ternary precursor includes: Step 1: Add the first mixed metal salt solution, precipitant, and complexing agent to the base solution, and react for 0.5h to 20h to obtain crystal nuclei; The components of the base liquid include water, ammonia water and liquid alkali; the mass concentration of the liquid alkali is 10%~40%, and the pH value of the base liquid is 10.5~12.5; the ammonia concentration in the base liquid is 0.5g / L~6g / L, and the mass concentration of ammonia water is 10%~30%; the temperature of the base liquid is 35℃~80℃; the base liquid is in a stirring state and the stirring speed is 100rpm~500rpm; protective gas is continuously introduced into the base liquid; The metal salts in the first mixed metal salt solution include a first nickel salt, a first cobalt salt and a first manganese salt, the molar ratio of Ni in the first nickel salt, Co in the first cobalt salt and Mn in the first manganese salt is x:y:(1-xy), and the total metal molar concentration in the first mixed metal salt solution is 1 mol / L to 1.5 mol / L; The precipitant is liquid alkali with a mass concentration of 10% to 40%, and the complexing agent is ammonia water with a mass concentration of 10% to 30%; The flow rate of the first mixed metal salt solution is 1L / h~4L / h; Step 2: Increase the rotation speed and ammonia concentration, keep the other conditions the same as step 1, and continue the reaction for 4h~12h to obtain crystals; Step 3: replacing the first mixed metal salt solution with the second mixed metal salt solution, and keeping the other conditions the same as step 2, and continuing the reaction until particles with a preset target particle size are obtained; Among them, the metal salts in the second mixed metal salt solution include a second nickel salt, a second cobalt salt and a second manganese salt, the molar ratio of Ni in the second nickel salt, Co in the second cobalt salt and Mn in the second manganese salt is x:y:(1-xy), and the total metal molar concentration in the second mixed metal salt solution is higher than the total metal molar concentration in the first mixed metal salt solution.
[0008] In an alternative embodiment, the D of the nucleus 50 1μm~2μm.
[0009] In an optional embodiment, in step 2, the rotation speed is increased to 1.5 to 3 times the rotation speed in step 1, and the ammonia concentration is increased to 3 to 5 times the ammonia concentration in step 1.
[0010] In an optional embodiment, the total metal molar concentration in the second mixed metal salt solution is 1.1 to 1.3 times the total metal molar concentration in the first mixed metal salt solution.
[0011] In an optional embodiment, the method further includes: aging, slurrying, washing, drying, screening and demagnetizing the particles of a preset target particle size.
[0012] In an optional embodiment, the slurrying is carried out using an aqueous NaOH solution with a concentration of 0.1 mol / L to 3 mol / L.
[0013] In a second aspect, the present invention provides a ternary precursor prepared by the preparation method of any one of the aforementioned embodiments.
[0014] In an optional embodiment, the primary particles of the ternary precursor are in the shape of laths, the primary particles are stacked vertically, and the vertical direction is the length direction of the laths.
[0015] In a third aspect, the present invention provides a ternary positive electrode material, the precursor of which is the ternary precursor of the aforementioned embodiment.
[0016] In a fourth aspect, the present invention provides a battery, wherein the positive electrode material of the battery is the ternary positive electrode material of the aforementioned embodiment.
[0017] The beneficial effects of the present invention include: In the preparation method of the ternary precursor provided by the present invention, the rotation speed and ammonia concentration are increased in step 2, so that the crystal nucleus obtained in step 1 is used as the growth point of the primary particle, and the crystal nucleus is vertically and orderly stacked and grown outwardly along the crystal nucleus. After a period of reaction, a crystal appears on the surface of the crystal nucleus, and the vertical stacking of the basic crystal is achieved by the oriented growth of the crystal, thereby obtaining a vertically stacked growth template. Then, the concentration of the mixed metal salt solution is increased in step 3, so as to increase the growth rate and growth power of the material, so that the material obtained by the precipitation reaction grows vertically quickly along the growth template. The preparation method is simple and easy to operate, and a precursor material with effective vertical stacking of primary particles can be obtained. The precursor can not only optimize the lithium ion channel, shorten the lithium ion transmission path, and improve the rate performance of the battery, but also has good compressive strength, can reduce microcracks caused by mechanical force, and improve the service life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0019] Figure 1 is a SEM image of the crystal core obtained in step 1 of Example 1; Figure 2 This is a SEM image of the crystal obtained in step 2 of Example 1; Figure 3 This is a SEM image of the ternary precursor obtained in step 3 of Example 1; Figure 4 This is a SEM image of the ternary precursor prepared in Comparative Example 1; Figure 5This is the SEM image of the ternary precursor prepared in Comparative Example 2. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0021] The following is a detailed description of the ternary precursor with vertically stacked primary particles provided by the present invention, as well as its preparation method and application.
[0022] The present invention provides a method for preparing a ternary precursor with primary particles vertically stacked. The chemical formula of the ternary precursor is Ni x Co y Mn 1-x-y (OH)2, wherein 0.5≤x≤0.8, 0.02≤y≤0.35, x+y<1.
[0023] The preparation of the ternary precursor comprises: Step 1: Add the first mixed metal salt solution, precipitant, and complexing agent to the base solution, react for 0.5h~20h, and obtain crystal nuclei.
[0024] The components of the base liquid include water, ammonia water and liquid alkali.
[0025] The mass concentration of ammonia water can be 10% to 30%, such as 10%, 15%, 20%, 25% or 30%, etc., or other values within the range of 10% to 30%. The addition of ammonia water is mainly used to control the ammonia concentration in the base liquid. For example, the ammonia concentration in the base liquid can be 0.5 g / L to 6 g / L, such as 0.5 g / L, 1 g / L, 1.5 g / L, 2 g / L, 2.5 g / L, 3 g / L, 3.5 g / L, 4 g / L, 4.5 g / L, 5 g / L, 5.5 g / L or 6 g / L, etc., or other values within the range of 0.5 g / L to 6 g / L.
[0026] The mass concentration of the liquid caustic soda can be 10% to 40%, such as 10%, 15%, 20%, 25%, 30%, 35% or 40%, etc., or other values within the range of 10% to 40%. The addition of the liquid caustic soda is mainly used to control the pH value in the base liquid. For example, the pH value of the base liquid can be 10.5 to 12.5, such as 10.5, 10.8, 11, 11.2, 11.5, 11.8, 12, 12.2 or 12.5, etc., or other values within the range of 10.5 to 12.5.
[0027] The temperature of the base liquid can be set to 35°C to 80°C, such as 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C, or other values within the range of 35°C to 80°C. The above temperature of the base liquid can be achieved by heating the mixture of water, ammonia water and liquid alkali.
[0028] The base liquid is in a stirring state and the stirring speed is 100rpm~500rpm. Exemplarily, the stirring speed can be 100rpm, 150rpm, 200rpm, 250rpm, 300rpm, 350rpm, 400rpm, 450rpm or 500rpm, etc., or it can be other values within the range of 100rpm~500rpm.
[0029] Protective gas can be continuously introduced into the base liquid.
[0030] The metal salt in the first mixed metal salt solution includes a first nickel salt, a first cobalt salt and a first manganese salt, and the molar ratio of Ni in the first nickel salt, Co in the first cobalt salt and Mn in the first manganese salt is x:y:(1-xy), which corresponds to the chemical formula of the ternary precursor. The first nickel salt, the first cobalt salt and the first manganese salt can be exemplarily in the form of sulfates, such as nickel sulfate, cobalt sulfate and manganese sulfate, and can also be in the form of nitrates and / or chlorides.
[0031] The total metal molar concentration in the first mixed metal salt solution is 1 mol / L~1.5 mol / L, such as 1 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L or 1.5 mol / L, etc., and can also be other values within the range of 1 mol / L~1.5 mol / L.
[0032] The precipitant is liquid alkali with a mass concentration of 10% to 40%, and the liquid alkali can be the same as the liquid alkali added to the base liquid.
[0033] The complexing agent is ammonia water with a mass concentration of 10% to 30% (such as 10%, 15%, 20%, 25% or 30%), and the ammonia water can be the same as the ammonia water added to the base liquid.
[0034] The flow rate of the first mixed metal salt solution may be 1 L / h to 4 L / h, such as 1 L / h, 1.5 L / h, 2 L / h, 2.5 L / h, 3 L / h, 3.5 L / h or 4 L / h, etc. The flow rate of the precipitant is adjusted to maintain a preset pH value, and the flow rate of the complexing agent is adjusted to maintain a preset ammonia value.
[0035] In some optional embodiments, the reaction time of step 1 can be 0.5h, 1h, 2h, 5h, 8h, 10h, 12h, 15h, 18h or 20h, etc., or other values within the range of 0.5h to 20h.
[0036] In some optional embodiments, the D of the obtained crystal core is 50 It can be 1μm~2μm.
[0037] Continuing from the above, step 1 can be understood as the nucleation stage in the preparation process of the ternary precursor. The crystal nuclei obtained in this stage are flocculent and have no obvious crystal structure.
[0038] Step 2: Increase the rotation speed and ammonia concentration, and keep the other conditions the same as step 1. Continue the reaction for 4h~12h to obtain crystals.
[0039] In some optional embodiments, the rotational speed in step 2 can be increased to 1.5 to 3 times the rotational speed in step 1, such as 1.5 times, 1.6 times, 1.7 times, 1.8 times, 1.9 times, 2.0 times, 2.1 times, 2.2 times, 2.3 times, 2.4 times, 2.5 times, 2.6 times, 2.7 times, 2.8 times, 2.9 times or 3 times, etc., or it can be other values within the range of 1.5 to 3 times.
[0040] By increasing the rotation speed, primary particle flakes with obvious crystalline structure can be formed. If the rotation speed is increased too little, it is not conducive to particle crystallization and the transformation from flocculent nuclei to primary particle nuclei cannot be achieved; if the rotation speed is increased too much, it is easy to cause growth stagnation, thereby changing the morphology and structure of the primary particles.
[0041] In some optional embodiments, the ammonia concentration in step 2 can be increased to 3 to 5 times the ammonia concentration in step 1, such as 3 times, 3.2 times, 3.5 times, 3.8 times, 4 times, 4.2 times, 4.5 times, 4.8 times or 5 times, etc., or it can be other values within the range of 3 to 5 times.
[0042] Oriented growth can be achieved by increasing the ammonia concentration. If the ammonia concentration is increased too little, it is not conducive to the change of primary particles and vertical primary particles cannot be obtained; if the ammonia concentration is increased too much, it is easy to cause the complexing ability of the system to change and the element ratio to deviate from the design value.
[0043] In some optional embodiments, the reaction time in step 2 can be 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h, 10h or 12h, etc., or other values within the range of 4h~12h.
[0044] Continuing from the above, step 2 can be understood as the crystallization period in the preparation process of the ternary precursor. In this stage, the crystal nucleus obtained in step 1 is used as the growth point of the primary particle, and the particles grow vertically and orderly along the crystal nucleus. After a period of reaction, crystals appear on the surface of the crystal nucleus, and the vertical stacking of the basic crystals is achieved through the oriented growth of the crystal, thereby obtaining a vertically stacked growth template.
[0045] Step 3: Replace the first mixed metal salt solution with the second mixed metal salt solution, keep the other conditions the same as step 2, and continue the reaction until particles with a preset target particle size are obtained.
[0046] Among them, the metal salts in the second mixed metal salt solution include a second nickel salt, a second cobalt salt and a second manganese salt, the molar ratio of Ni in the second nickel salt, Co in the second cobalt salt and Mn in the second manganese salt is x:y:(1-xy), and the total metal molar concentration in the second mixed metal salt solution is higher than the total metal molar concentration in the first mixed metal salt solution.
[0047] It can be understood that the molar ratio of Ni, Co and Mn in the second mixed metal salt solution is the same as that in the first mixed metal salt solution, except that the concentration of each metal salt is increased.
[0048] In some optional embodiments, the total metal molar concentration in the second mixed metal salt solution is 1.1 to 1.3 times the total metal molar concentration in the first mixed metal salt solution, such as 1.1 times, 1.15 times, 1.2 times, 1.25 times or 1.3 times, etc., and may also be other values within the range of 1.1 to 1.3.
[0049] By increasing the concentration of the mixed metal salt solution in this step, the growth rate and growth power of the material can be increased, so that the material obtained by the precipitation reaction can grow vertically quickly along the growth template. If the concentration of the mixed metal salt solution is increased too little, the growth rate will be too slow, and in this process, part of the material obtained by the precipitation reaction may grow in other directions; if the concentration of the mixed metal salt solution is increased too much, the concentration of the local reaction system is likely to be too high, resulting in the material being nucleated alone at that location, making it difficult to grow uniformly.
[0050] Continuing from the above, step 3 can be understood as the growth period in the preparation process of the ternary precursor. In this stage, the material achieves rapid growth in the vertical direction, and basically no lateral growth occurs.
[0051] Furthermore, the obtained particles of the preset target particle size can be aged, slurried, washed, dried, screened and demagnetized.
[0052] Aging can be carried out in an aging kettle, and the aging time can be 8h~12h. After aging, filter, add the filter cake to a NaOH aqueous solution with a concentration of 0.1mol / L~3mol / L for slurry. After slurry, filter, wash the filtered filter cake until the pH value of the filtrate is less than 9, and then dry, screen and demagnetize the washed filter cake.
[0053] Correspondingly, the present invention also provides a ternary precursor, which is prepared by the above preparation method.
[0054] The primary particles of the ternary precursor are in the shape of laths, and the primary particles are stacked vertically.
[0055] The above-mentioned "vertical stacking" can be understood as: vertical growth outward along the surface of the crystal core, that is, the vertical direction is the length direction of the lath. In other words, the length direction of the primary particle is not circumferentially or laterally extending along the surface of the crystal core, but vertically extending outward along the surface of the crystal core similar to radially.
[0056] The ternary precursor with the above characteristics has a shorter ion channel after sintering, which is conducive to the insertion and extraction of lithium ions, and can improve the rate performance of the ternary positive electrode material. In addition, the ternary precursor with the above characteristics also has better compressive strength, can avoid or reduce microcracks caused by mechanical force, which is beneficial to improve the cycle performance of the battery and extend the service life of the battery.
[0057] In some optional embodiments, the size of the ternary precursor does not exceed 5 μm.
[0058] In addition, the present invention also provides a ternary positive electrode material, the precursor of which is the ternary precursor of the aforementioned embodiment.
[0059] Furthermore, the present invention also provides a battery, the positive electrode material of the battery is the above-mentioned ternary positive electrode material.
[0060] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0061] Example 1 This embodiment provides a ternary precursor, and the preparation method thereof is as follows: Step 1: Add the first mixed metal salt solution, precipitant, and complexing agent to the base solution and react for 8 hours to obtain a crystal nucleus (such as Figure 1 as shown).
[0062] The components of the base liquid include water, ammonia water and liquid alkali.
[0063] The mass concentration of ammonia water is 15%, and the ammonia concentration in the bottom liquid is 4g / L. The concentration of liquid alkali is 22wt%, and the pH value of the bottom liquid can be 11.9. The temperature of the bottom liquid is 50°C, the bottom liquid is in a stirring state, and the stirring speed is 300rpm. Nitrogen can be continuously introduced into the bottom liquid.
[0064] The metal salts in the first mixed metal salt solution are nickel sulfate, cobalt sulfate and manganese sulfate, and the molar ratio of Ni in nickel sulfate, Co in cobalt sulfate and Mn in manganese sulfate is 0.7:0.1:0.2. The total metal molar concentration in the first mixed metal salt solution is 1.1 mol / L.
[0065] The precipitant is liquid alkali with a mass concentration of 22wt%, which is the same as the liquid alkali added to the base liquid.
[0066] The complexing agent is ammonia water with a mass concentration of 15%, which is the same as the ammonia water added to the base liquid.
[0067] The flow rate of the first mixed metal salt solution is 2 L / h, the flow rate of the precipitant is adjusted to maintain the pH at 11.9, and the flow rate of the complexing agent is adjusted to maintain the ammonia concentration at 4 g / L.
[0068] The D of the resulting nucleus 50 is 1.5μm.
[0069] Step 2: Increase the speed to 500 rpm and the ammonia concentration to 16 g / L. Keep the other conditions the same as step 1. Continue the reaction for 12 hours. The surface of the crystal nucleus grows from disordered crystal nuclei to regular crystals (such as Figure 2 As shown in Figure 3), the primary particles are stacked vertically.
[0070] Step 3: Replace the first mixed metal salt solution with the second mixed metal salt solution, and keep the other conditions the same as step 2, and react until the preset target particle size (D 50 = 3.5 μm) (e.g. Figure 3 During this stage, the primary particles at each point continue to grow outwards and are distributed radially.
[0071] The metal salts in the second mixed metal salt solution are nickel sulfate, cobalt sulfate and manganese sulfate, and the molar ratio of Ni in nickel sulfate, Co in cobalt sulfate and Mn in manganese sulfate is 0.7:0.1:0.2. The total metal molar concentration in the second mixed metal salt solution is 1.45 mol / L.
[0072] Step 4: The obtained particles of the preset target particle size are aged in an aging kettle for 10 hours. After aging, the filter cake is filtered and a 2 mol / L NaOH aqueous solution is added to slurry. After slurry, the filter cake is filtered and washed until the pH value of the filtrate is less than 9, and then the washed filter cake is dried, sieved and demagnetized.
[0073] Example 2 This embodiment provides a ternary precursor, and the preparation method thereof is as follows: Step 1: Add the first mixed metal salt solution, precipitant and complexing agent into the base liquid, react for 0.5h to obtain crystal nuclei.
[0074] The components of the base liquid include water, ammonia water and liquid alkali.
[0075] The mass concentration of ammonia water is 10%, and the ammonia concentration in the bottom liquid can be 0.5g / L. The concentration of liquid alkali is 20wt%, and the pH value of the bottom liquid can be 10.5. The temperature of the bottom liquid is 35°C, the bottom liquid is in a stirring state, and the stirring speed is 100rpm. Nitrogen can be continuously introduced into the bottom liquid.
[0076] The metal salts in the first mixed metal salt solution are nickel sulfate, cobalt sulfate and manganese sulfate, and the molar ratio of Ni in nickel sulfate, Co in cobalt sulfate and Mn in manganese sulfate is 0.7:0.1:0.2. The total metal molar concentration in the first mixed metal salt solution is 1 mol / L.
[0077] The precipitant is liquid alkali with a mass concentration of 20wt%, which is the same as the liquid alkali added to the base liquid.
[0078] The complexing agent is ammonia water with a mass concentration of 10%, which is the same as the ammonia water added to the base liquid.
[0079] The flow rate of the first mixed metal salt solution is 1 L / h, the flow rate of the precipitant is adjusted to maintain the pH at 11.9, and the flow rate of the complexing agent is adjusted to maintain a preset ammonia value.
[0080] The D of the resulting nucleus 50 It is 1.1μm.
[0081] Step 2: Increase the rotation speed to 300 rpm and increase the ammonia concentration to 2.5 g / L. Keep the other conditions the same as step 1. Continue the reaction for 10 hours. The surface of the crystal nucleus grows from disordered crystal nuclei to regular crystals, and the primary particles are vertically stacked.
[0082] Step 3: Replace the first mixed metal salt solution with the second mixed metal salt solution, and keep the other conditions the same as step 2, and react until the preset target particle size (D 50=3.5μm). During this stage, the primary particles at each point continue to grow outwards and are distributed radially.
[0083] The metal salts in the second mixed metal salt solution are nickel sulfate, cobalt sulfate and manganese sulfate, and the molar ratio of Ni in nickel sulfate, Co in cobalt sulfate and Mn in manganese sulfate is 0.7:0.1:0.2. The total metal molar concentration in the second mixed metal salt solution is 1.1 mol / L.
[0084] Step 4: The obtained particles of the preset target particle size are aged in an aging kettle for 10 hours. After aging, the filter cake is filtered and a 0.1 mol / L NaOH aqueous solution is added to the filter cake for slurry. After slurrying, the filter cake is filtered and washed until the pH value of the filtrate is less than 9, and then the washed filter cake is dried, sieved and demagnetized.
[0085] Example 3 This embodiment provides a ternary precursor, and the preparation method thereof is as follows: Step 1: Add the first mixed metal salt solution, precipitant and complexing agent to the base solution and react for 20 hours to obtain crystal nuclei.
[0086] The components of the base liquid include water, ammonia water and liquid alkali.
[0087] The mass concentration of ammonia water is 30%, and the ammonia concentration in the bottom liquid can be 6g / L. The concentration of liquid alkali is 25wt%, and the pH value of the bottom liquid can be 12.5. The temperature of the bottom liquid is 80°C, the bottom liquid is in a stirring state, and the stirring speed is 500rpm. Nitrogen can be continuously introduced into the bottom liquid.
[0088] The metal salts in the first mixed metal salt solution are nickel sulfate, cobalt sulfate and manganese sulfate, and the molar ratio of Ni in nickel sulfate, Co in cobalt sulfate and Mn in manganese sulfate is 0.7:0.1:0.2. The total metal molar concentration in the first mixed metal salt solution is 1.5 mol / L.
[0089] The precipitant is liquid alkali with a mass concentration of 25wt%, which is the same as the liquid alkali added to the base liquid.
[0090] The complexing agent is ammonia water with a mass concentration of 30%, which is the same as the ammonia water added to the base liquid.
[0091] The flow rate of the first mixed metal salt solution is 4 L / h, the flow rate of the precipitant is adjusted to maintain the pH at 11.9, and the flow rate of the complexing agent is adjusted to maintain a preset ammonia value.
[0092] The D of the resulting nucleus 50 It is 1.7μm.
[0093] Step 2: Increase the rotation speed to 750 rpm and increase the ammonia concentration to 18 g / L. Keep the other conditions the same as step 1. Continue the reaction for 4 hours. The surface of the crystal nucleus grows from disordered crystal nuclei to regular crystals, and the primary particles are vertically stacked.
[0094] Step 3: Replace the first mixed metal salt solution with the second mixed metal salt solution, and keep the other conditions the same as step 2, and react until the preset target particle size (D 50 =3.5μm). During this stage, the primary particles at each point continue to grow outwards and are distributed radially.
[0095] The metal salts in the second mixed metal salt solution are nickel sulfate, cobalt sulfate and manganese sulfate, and the molar ratio of Ni in nickel sulfate, Co in cobalt sulfate and Mn in manganese sulfate is 0.7:0.1:0.2. The total metal molar concentration in the second mixed metal salt solution is 1.95 mol / L.
[0096] Step 4: The obtained particles of the preset target particle size are aged in an aging kettle for 10 hours. After aging, the filter cake is filtered and a 3 mol / L NaOH aqueous solution is added to slurry. After slurrying, the filter cake is filtered and washed until the pH value of the filtrate is less than 9, and then the washed filter cake is dried, sieved and demagnetized.
[0097] Comparative Example 1 The difference between this comparative example and Example 1 is that in step 2, the rotation speed is increased by 1.33 times, and the ammonia concentration is maintained at 4 g / L in step 1.
[0098] At the end of step 2 of this comparative example, most of the surface of the crystal nucleus is disordered crystals, with a small amount of high-crystallinity crystals, and the surface morphology is obviously different at each point; after entering the growth period, a vertically stacked primary particle structure cannot be formed, and the primary particles on the surface are quite different. Affected by the morphology, some physical and chemical indicators cannot meet the standards and are treated as waste.
[0099] The SEM image of the ternary precursor obtained in this comparative example is as follows Figure 4 shown.
[0100] Comparative Example 2 The difference between this comparative example and Example 1 is that the second mixed metal salt solution used in step 3 is equal to the first mixed metal salt solution used in steps 1 and 2 and is unchanged.
[0101] During the growth period of the comparative example, the primary particles grew slowly, and some particles grew horizontally.
[0102] The SEM image of the ternary precursor obtained in this comparative example is as follows Figure 5 shown.
[0103] Comparative Example 3 The difference between this comparative example and Example 1 is that in step 2, the rotation speed is increased to 3.5 times the rotation speed in step 1, and the ammonia concentration is kept equal to that in step 1.
[0104] Comparative Example 4 The difference between this comparative example and Example 1 is that in step 2, the rotation speed is kept equal to that in step 1, and the ammonia concentration is increased to 2.5 times the ammonia concentration in step 1.
[0105] Comparative Example 5 The difference between this comparative example and Example 1 is that in step 2, the rotation speed is kept equal to that in step 1, and the ammonia concentration is increased to 5.5 times the ammonia concentration in step 1.
[0106] Comparative Example 6 The difference between this comparative example and Example 1 is that in step 2, the rotation speed and the ammonia concentration are kept equal to those in step 1.
[0107] Comparative Example 7 The difference between this comparative example and Example 1 is that in step 3, the total metal molar concentration in the second mixed metal salt solution is twice the total metal molar concentration in the first mixed metal salt solution. The second mixed salt concentration is relatively high, and fine powder appears during the preparation process, which is treated as waste.
[0108] Comparative Example 8 The difference between this comparative example and Example 1 is that in step 1, the ammonia concentration in the base liquid is 8 g / L.
[0109] Comparative Example 9 The difference between this comparative example and Example 1 is that in step 1, the stirring speed is 600 rpm.
[0110] Comparative Example 10 The difference between this comparative example and Example 1 is that the total metal molar concentration in the first mixed metal salt solution is 2 mol / L.
[0111] Test example The ternary precursors obtained in the above Examples 1 to 3 and Comparative Examples 1 to 10 were prepared into ternary positive electrode materials and further assembled into button batteries. The performances of the obtained batteries were compared, and the results are shown in Table 1.
[0112] The process of preparing the ternary precursor into the ternary positive electrode material is as follows: the precursor and lithium hydroxide are evenly mixed in a molar ratio of 1:1.05, sintered at 700°C, taken out and ground to finally obtain the positive electrode material.
[0113] The process of assembling the ternary positive electrode material into a button cell is as follows: the positive electrode material: conductive carbon: polyvinylidene fluoride (PVDF) = 90:5:5 is mixed into a slurry to make a positive electrode sheet, and the metal lithium sheet is used as the negative electrode material to assemble into a button cell. The button cell is tested for electrochemical performance under 1C, 3.0V~4.35V conditions.
[0114] Defect rate: The precursor material is coated on an aluminum foil sheet, and a 0.2 kg cylinder is used to perform a single rolling test on the material surface. Then, a sample of the material after rolling is taken and the percentage of cracked or deformed particles is obtained through a scanning electron microscope to determine the compressive strength of the precursor material. The lower the defect rate, the better the compressive strength of the precursor material, and vice versa.
[0115] Table 1 Test results
[0116] It can be seen from Table 1 that the ternary precursor prepared in the embodiment of the present invention is conducive to further preparing a battery with both high rate performance and compressive strength.
[0117] In summary, the preparation method of the ternary precursor provided by the present invention is simple and easy to operate, and a precursor material with vertically stacked primary particles can be obtained. The ternary precursor can not only optimize the lithium ion channel, shorten the lithium ion transmission path, and improve the rate performance of the battery, but also has good compressive strength, can reduce microcracks caused by mechanical force, and improve the service life of the battery.
[0118] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a ternary precursor with vertically stacked primary particles, characterized in that: The chemical formula of the ternary precursor is Ni x Co y Mn 1-x-y (OH)2, where 0.5≤x≤0.8, 0.02≤y≤0.35, x+y<1; The preparation of the ternary precursor comprises: Step 1: Add the first mixed metal salt solution, precipitant, and complexing agent to the base solution, and react for 0.5h to 20h to obtain crystal nuclei; The base liquid comprises water, ammonia water and liquid alkali; the mass concentration of the liquid alkali is 10% to 40%; the pH value of the base liquid is 10.5 to 12.5; the ammonia concentration in the base liquid is 0.5 g / L to 6 g / L, and the mass concentration of the ammonia water is 10% to 30%; the temperature of the base liquid is 35° C. to 80° C.; the base liquid is in a stirring state and the stirring speed is 100 rpm to 500 rpm; a protective gas is continuously introduced into the base liquid; The metal salts in the first mixed metal salt solution include a first nickel salt, a first cobalt salt and a first manganese salt, the molar ratio of Ni in the first nickel salt, Co in the first cobalt salt and Mn in the first manganese salt is x:y:(1-xy), and the total metal molar concentration in the first mixed metal salt solution is 1 mol / L to 1.5 mol / L; The precipitant is liquid alkali with a mass concentration of 10% to 40%, and the complexing agent is ammonia water with a mass concentration of 10% to 30%; The flow rate of the first mixed metal salt solution is 1 L / h to 4 L / h; Step 2: Increase the rotation speed and ammonia concentration, keep the other conditions the same as step 1, and continue the reaction for 4h~12h to obtain crystals; Step 3: replacing the first mixed metal salt solution with the second mixed metal salt solution, and keeping the other conditions the same as step 2, and continuing the reaction until particles with a preset target particle size are obtained; Wherein, the metal salts in the second mixed metal salt solution include a second nickel salt, a second cobalt salt and a second manganese salt, the molar ratio of Ni in the second nickel salt, Co in the second cobalt salt and Mn in the second manganese salt is x:y:(1-xy), and the total metal molar concentration in the second mixed metal salt solution is higher than the total metal molar concentration in the first mixed metal salt solution.
2. The preparation method according to claim 1, characterized in that: The D of the crystal nucleus 50 1μm~2μm.
3. The preparation method according to claim 1 or 2, characterized in that: In step 2, the rotation speed is increased to 1.5 to 3 times of the rotation speed in step 1, and the ammonia concentration is increased to 3 to 5 times of the ammonia concentration in step 1.
4. The preparation method according to claim 1 or 2, characterized in that: The total metal molar concentration in the second mixed metal salt solution is 1.1 to 1.3 times the total metal molar concentration in the first mixed metal salt solution.
5. The preparation method according to claim 1, characterized in that: Also includes: The particles of the preset target particle size are aged, slurried, washed, dried, sieved and demagnetized.
6. The preparation method according to claim 5, characterized in that: The slurrying is carried out using a NaOH aqueous solution with a concentration of 0.1 mol / L to 3 mol / L.
7. A ternary precursor, characterized in that: The method is prepared by any one of claims 1 to 6.
8. The ternary precursor according to claim 7, characterized in that: The primary particles of the ternary precursor are in the shape of laths, and the stacking mode of the primary particles is vertical stacking, and the vertical direction is the length direction of the laths.
9. A ternary positive electrode material, characterized in that: The precursor of the ternary positive electrode material is the ternary precursor described in claim 8.
10. A battery, characterized in that: The positive electrode material of the battery is the ternary positive electrode material as claimed in claim 9.
Citation Information
Patent Citations
Novel continuous method for preparing nickel cobalt lithium manganate precursor
CN114014376A
Method for preparing single-crystal ternary precursor
CN116199272A
Preparation method of large-particle high-nickel ternary precursor material and large-particle high-nickel ternary precursor material
CN116375104A
Method for improving cracks of high-nickel large-particle ternary precursor
CN118145719A
Ultrahigh-nickel ternary precursor and preparation method therefor
WO2023179247A1